Factores asociados a enfermedad pulmonar intersticial en pacientes con artritis reumatoide en el servicio de Reumatología del Hospital IV Víctor Lazarte Echegaray durante el periodo 2019-2020 - Otoya Guzmán, Claudia Rosana (2022)
Interstitial lung disease is a frequent extra-articular manifestation in patients with rheumatoid arthritis that represents a great impact on the quality of life of patients, as well as on their prognosis. In the present project, the association of smoking, male sex, advanced age and positivity for the anti-cyclic citrullinated peptide antibody with interstitial lung disease in patients with rheumatoid arthritis is sought.